Determination of Pyridaphenthion in Aqueous and Food Samples by Reverse Phase High Performance Liquid Chromatography (HPLC) after QuEChERS Extraction and Degradation Studies under Ultraviolet (UV) Radiation - Chormey, Dotse Selali; Yilmaz Durak, Busra; Bakirdere, Sezgin (TAYLOR & FRANCIS INC, 2021)
This study employed QuEChERS as an efficient sample clean-up and extraction method for the determination of pyridaphenthion in aqueous, fruit and vegetable samples by high performance liquid chromatography (HPLC) coupled with ultraviolet (UV) detection. All of the instrumental parameters were carefully optimized to obtain a sharp analyte signal eluted at an short retention time. The analyte was eluted on a C18 column using an isocratic mobile phase system that was composed of 40:60 (v/v) water:acetonitrile. The linear working range of pyridaphenthion was from 10 mu g/L to 50 mg/L, and the respective limits of detection and quantification were determined to be 2.4 and 8.1 mu g/L. The instrumental precision was very good with a relative standard deviation value of 1.8%. Spike recovery studies were used to validate the accuracy and applicability of the method for food and aqueous samples. Degradation studies for pyridaphenthion under UV radiation were also performed with a liquid chromatography quadrupole time of flight mass spectrometer.
Keywords: High performance liquid chromatography (HPLC); pesticide; pyridaphenthion; quick easy cheap efficient rugged safe; ultraviolet (UV) irradiation; PESTICIDE EXPOSURE; MASS-SPECTROMETRY; INSECTICIDE; GROWTH; Chemistry